2017
DOI: 10.1097/ta.0000000000001374
|View full text |Cite
|
Sign up to set email alerts
|

Daily propranolol administration reduces persistent injury-associated anemia after severe trauma and chronic stress

Abstract: Background Following severe trauma, patients develop a norepinephrine-mediated persistent, injury-associated anemia. This anemia is associated with suppression of bone marrow erythroid colony growth, along with decreased iron levels, and elevated erythropoietin (EPO) levels, which are insufficient to promote effective erythropoiesis. The impact of norepinephrine on iron regulators such as ferroportin, transferrin and transferrin receptor-1 (TFR-1) are unknown. Using a clinically relevant rodent model of lung c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 41 publications
4
21
1
1
Order By: Relevance
“…In a separate sequential study, the authors observed an increase in Hgb levels with propranolol. (46). The latter model varies with a superimposed chronic stress to the hemorrhagic shock where the bone marrow cellularity was altered.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate sequential study, the authors observed an increase in Hgb levels with propranolol. (46). The latter model varies with a superimposed chronic stress to the hemorrhagic shock where the bone marrow cellularity was altered.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] In preclinical rodent studies of blunt trauma, hemorrhagic shock and chronic stress, postinjury hypercatecholaminemia is associated with a suppression of bone marrow erythroid progenitor growth, reduced erythroid commitment, an abnormal EPO response, prolonged mobilization of hematopoietic progenitor cells, and dysregulation of iron homeostasis. 11,12 Norepinephrine, a key modulator of hematopoietic progenitor mobilization and an inhibitor of bone marrow erythroid cell growth, also directly stimulates IL-6 release, and several of our prior studies have implicated these cytokines directly in the development of persistent injury-associated anemia. 13,14 Tumor necrosis factor-alpha (TNF-a) and interleukin-6 (IL-6) are both proinflammatory cytokines that influence hematopoiesis and have altered expression following severe trauma.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Dysfunctional erythropoiesis in a rodent trauma model can be ameliorated with chemical sympathectomy using either propranolol or clonidine, suggesting that a reduction of hypercatecholaminemia improves erythropoiesis. [11][12][13][21][22][23][24][25][26] Prior research has evaluated the postinjury inflammatory state in severely injured trauma patients and demonstrated their erythropoietic dysfunction and iron dysregulation. 27 To validate our preclinical findings and to expand upon our prior study of the postinjury inflammatory state in humans, the purpose of this study was to evaluate additional severely injured trauma patients and determine if there is a relationship between the ISS in trauma patients, and the degree of neuroendocrine activation and systemic inflammation that is related with persistent injury-associated anemia as well as to further characterize the bone marrow response to injury.…”
Section: Introductionmentioning
confidence: 99%
“…42 These miR findings correlate with our previous studies demonstrating significant erythroid growth suppression after LCHS/CS and improvement in inflammation and erythropoiesis with the use of propranolol after LCHS/CS. 3,13,14,43 Also, bone marrow miR-130b expression was suppressed in the LCHS/CS group compared with LCHSþBB and naïve rodents. Previous studies have demonstrated that miR-130b downregulation played a role in prostate and pancreatic cancer, likely through its targeting of STAT3.…”
Section: Discussionmentioning
confidence: 91%
“…[9][10][11][12] In addition, both human and rodent studies have demonstrated that a reduction in hypercatecholaminemia and inflammation with propranolol or clonidine can mitigate this persistent injury-associated anemia and improve bone marrow erythropoietic function. 3,[13][14][15] Therefore, continuing to focus on potential targets of inflammatory processes would provide novel treatment strategies for the treatment of erythropoietic dysfunction after trauma.…”
mentioning
confidence: 99%